Ontology and protocol secure for SCADA. (11th April 2014) - Nabil, Sahli; Mohamed, Benmohammed; Bourennane, El–Bay
In this work, we present a semantic cyber security system and we study its semantic intelligent systems vulnerabilities, focusing on the semantic attacks. For resolving semantic problems we propose a security global solution for the new generation of SCADA systems. The proposed solution aims at protecting critical semantic SCADA processes from the effects of major failures and semantic vulnerabilities in the modern IT–SCADA network. We used a security block in the global network access point, security protocols deployed in different network (OSI) levels and security ontologies deployed in security devices. We used our mixed coordinates (ECC) cryptography solution, this is an encryption technology developed specifically for low latency embedded applications. We integrated security mechanisms in specific SCADA protocols as Modbus. Moreover, we made use of the WS–Security framework and we crypt and signed all the improved security protocols frames with our mixed (ECC) and a hash function.